INSTALLATION OF SMART FARM SERVER FOR DATA MONITORING VIA MOBILE APPLICATION - รัตนนิมิตร, วริศร์; เกษพานิช, วุฒิชัย; ชุนประวัติ, สุทธิลักษณ์ (Journal of Energy and Environment Technology of Graduate School Siam Technology College, 2019)
Internet of Things (IoT) is part of the internet that envisions all objects around us. IoT has a very wide and includes variety of objects like electronics product i.e. smart phones, tablets, digital cameras and sensors. and agricultural system in order to add a product value in quality, This research aim to propose a model for Tracking agricultural data via Internet of things. Using NodeMCU Microcontroller for receive Soil Moisture, Temperature and Humidity data from verities sensors, and send data via WIFI to Blynk Server for generate Soil Moisture , temperature and humidity graph and controlling Water Pump with Mobile Application also.